2018
DOI: 10.17159/2411-9717/2018/v118n2a7
|View full text |Cite
|
Sign up to set email alerts
|

Production of metallurgical-grade silicon from Egyptian quartz

Abstract: Metallurgical-grade silicon (MG-Si) is an important metal which has a range of diverse industrial applications such as a deoxidizer in steelmaking industry, alloying element in the aluminum industry, the preparation of organosilanes, and the production of hyperpure 'electronic grade' silicon (>99.99% Si), which is used in the electronics industry as well as solar cells (PV Education. 2013; Aasly, 2008). MG-silicon is produced by the carbothermic reduction-smelting process, in which silica is reduced by carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…It was reported that a current efficiency of about 87% and an energy consumption of 10 kW h/kg-Si were obtained when 1.0 mm depth of quartz was reduced. 42 In comparison with the energy consumption of the Siemens process (about 120−200 kW h/kg-Si) 53 and metallurgicalgrade silicon (>20 kW h/kg-Si), 7,54 this molten salt electrolysis technology shows a bright prospect for future industrialization and application in LIBs because of its much lower energy consumption.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…It was reported that a current efficiency of about 87% and an energy consumption of 10 kW h/kg-Si were obtained when 1.0 mm depth of quartz was reduced. 42 In comparison with the energy consumption of the Siemens process (about 120−200 kW h/kg-Si) 53 and metallurgicalgrade silicon (>20 kW h/kg-Si), 7,54 this molten salt electrolysis technology shows a bright prospect for future industrialization and application in LIBs because of its much lower energy consumption.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…It is known that the production of technical silicon is carried out in single-or three-phase furnaces with two or three graphite electrodes, where melting is carried out mainly on high-quality quartzite (SiO2 > 98 %) using charcoal, petroleum coke and coal as a reducing agent [13]. For loosening the сcharge in large furnaces (> 6 MVA), wood chips are usually applied.…”
Section: Experimental Partmentioning
confidence: 99%
“…The exothermic nature of calcium-silica reaction, which has potential explosion, made it impractical for calciothermic process (Houli et al, 2018). Recently, Ali, El-Sadek, Morsi, El-Barawy, & Abou-Shahba (2018) reported the carbothermic reduction process of Egyptian quartz using the high power of electrical furnace to recover about 75% polysilicon with about 97% purity. Several researchers carried out a magnesiothermic reduction of silica at a temperature between 600-950 o C. A maximum Si yield more than 99.9% was achieved (Barati, Sarder, McLean, & Roy, 2011;Won, Nersisyan, & Won, 2011;Larbi, Barati, & McLean, 2013;Swatsitang & Krochai, 2009;Houli et al, 2018).…”
Section: Introductionmentioning
confidence: 99%